George's Marvellous medicine - Roald Dahl (UK Puffin Books, 2013)
George is a young boy who lives on a farm with his parents and his extremely grumpy and mean Grandma. She constantly bullies George and complains about everything. One day, while alone at home with her, George decides to make a new kind of medicine to replace the one Grandma takes every day. He goes around the house collecting strange and wild ingredients from the bathroom, kitchen, shed$1 (Beven animal food$1 (Band mixes them all together in a huge pot to create his "marvellous medicine." When Grandma takes the medicine, she grows suddenly very tall, shooting through the roof! His parents are shocked, especially his father, who sees this as a chance to make lots of money if they can reproduce the medicine for farm animals. George tries to make more versions, but none work the same way. Eventually, Grandma drinks a failed version of the medicine and shrinks so much she disappears completely!s